An epoxy thiolactone on stage: four component reactions, synthesis of poly(thioether urethane)s and the respective hydrogels. Issue 12 (7th March 2016) - Mommer, Stefan; Truong, Khai-Nghi; Keul, Helmut; Möller, Martin
Abstract : An epoxy thiolactone was developed as a versatile platform for multicomponent reactions, the synthesis of poly(thioether urethane)s or hydrogels containing epoxy groups. Abstract : The synthesis of an epoxy thiolactone is described. The reactivity of this epoxy thiolactone towards amines is evaluated and presented in a four component reaction. Upon ring opening of the thiolactone with an amine an AB-type epoxy thiol monomer is generated which in situ starts a thiol–epoxy polymerization. The polymerization mechanism and kinetics are investigated: the influence of different parameters such as solvent, substrate concentration, and catalyst on the reaction course is explored. Finally, concepts for the formation of reactive hydrogels are presented.